(untitled) (Research, Society and Development, 2021)
The solid albumen of the green coconut is a co-product of the coconut water industry that has high nutritional quality, but is widely wasted in Brazil. The aim of this study was to evaluate of using this co-product in the production of mixed coconut and pineapple sweet and to characterize them. Three formulations were prepared (F1 4.8% pineapple and coconut, F2 green coconut 50%, pineapple 24.25% and F3 green coconut 59.7% and pineapple 10%) and microbiological, physical-chemical and sensory analyzes were performed (acceptance and purchase intention). The results revealed that all formulations were safe for human consumption with counts below the detection limit (<100 Log UFC / mL) for Enterobacteria and Molds and yeasts and the absence of Salmonella spp. All formulations were presented with acidic pH, with the highest acidity (p <0.05) in the formulations with the highest amount of pineapple. In the sensory evaluation, all formulations were accepted with scores above the neutral point, but the F1 formulation received higher concepts and a higher percentage of purchase intention whereas F3 obtained the highest percentage of rejection in purchase intention. The use of solid green coconut albumen presented itself as an alternative for use in the production of coconut and pineapple candy, resulting in microbiologically safe products, with physico-chemical characteristics within the scope of the legislation and well accepted by the senses, being, therefore, an alternative to combat the waste of this raw material in Brazil.